Stakeholder Analysis of a Cervical Cancer Program at Wangon Community Health Center, Banyumas Regency, Based on the Power-Interest Grid - Renda Aldilawati; Yuditha Nindya; Arif Kurniawan (Insights in Public Health Journal, 2025)
Background: Banyumas Regency has experienced consecutive increases in cervical cancer cases in 2019, 2020, and 2021, with 213, 305, and 589 cases respectively. This is one reason the Banyumas government is implementing cervical cancer control measures, including HPV immunization and early detection (screening) through Visual Inspection with Acetic Acid (VIA) or Pap smears. However, the overall achievement rate for VIA screening across community health centers (CHC) in Banyumas Regency remains below target, including at the Wangon Health Center. Wangon Health Center has implemented various cervical cancer programs involving multiple stakeholders. Yet, the achievement of its early detection program often falls short of the target (10% of all Women of Reproductive Age annually), and support from cross-sectoral stakeholders remains insufficient as they do not provide recommendations or follow-up on screening program outcomes. Therefore, a stakeholder analysis is needed to determine the extent of stakeholder roles in optimizing program success. Methods: This research was conducted in the working area of Wangon I Health Center from October to December 2024 using a qualitative design and a case study approach. Informants were selected via purposive and snowball sampling. The study involved 6 primary informants: the head of the health center, the Maternal and Child Health (KIA) program officer, the immunization program officer, a community health volunteer, a community member, and 2 supporting informants: The Family Planning Field Worker (PLKB) and the Family Welfare Empowerment (PKK) representative. Data analysis utilized thematic analysis. Results: Involved stakeholders have distinct roles. These were categorized into three groups: key stakeholders as policy or program makers, primary stakeholders as implementers, targets, and main information disseminators for the program, and secondary stakeholders as supporters and program information conduits. Based on power and interest, they were classified into: high power-high interest (key players) as routine policymakers; high power-low interest (keep satisfied) as parties with high power but low direct interest in the program; low power-high interest (keep informed) as implementers and disseminators of cervical cancer program information/education; and low power-low interest (minimal effort) as program targets. Conclusions: Stakeholders in the early detection of cervical cancer have varying levels of involvement and influence, necessitating optimization of each stakeholder's role. Based on the findings, the health center, as the program holder, needs to enhance collaboration with cross-sectoral partners through educational activities and screening participant recruitment in schools (with the education sector) and can conduct educational campaigns by distributing posters, banners, or leaflets to every village in the Wangon I Health Center area.